2023
DOI: 10.3390/antiox12051110
|View full text |Cite
|
Sign up to set email alerts
|

Lignan-Rich Sesame (Sesamum indicum L.) Cultivar Exhibits In Vitro Anti-Cholinesterase Activity, Anti-Neurotoxicity in Amyloid-β Induced SH-SY5Y Cells, and Produces an In Vivo Nootropic Effect in Scopolamine-Induced Memory Impaired Mice

Abstract: Alzheimer’s disease, a major cause of dementia, is characterized by impaired cholinergic function, increased oxidative stress, and amyloid cascade induction. Sesame lignans have attracted considerable attention owing to their beneficial effects on brain health. This study investigated the neuroprotective potential of lignan-rich sesame cultivars. Among the 10 sesame varieties studied, Milyang 74 (M74) extracts exhibited the highest total lignan content (17.71 mg/g) and in vitro acetylcholinesterase (AChE) inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…As part of our ongoing interest in exploring anti-AD and anti-ageing drug candidates from natural sources [ 22 , 23 ], encouraged by the reported AChE-inhibitory effects of furofuranoid lignans [ 13 , 14 , 15 ], the isolated lignans 1 – 5 were evaluated for anti-AChE activity as well as their ability to boost telomerase activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of our ongoing interest in exploring anti-AD and anti-ageing drug candidates from natural sources [ 22 , 23 ], encouraged by the reported AChE-inhibitory effects of furofuranoid lignans [ 13 , 14 , 15 ], the isolated lignans 1 – 5 were evaluated for anti-AChE activity as well as their ability to boost telomerase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Schweinf. (Asclepiadaceae), and Sesamum indicum L. (Acanthaceae) plant species exhibited potent AChE-inhibitory activity [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sesame seeds (Sesamum indicum L.) contain a multitude of phenolic compounds, which exhibit beneficial effects on human health. Phenolic components, known for their antioxidant, anti-inflammatory and hypolipidemic activities, and, specifically, sesame lignans like sesamin and sesamolin have attracted large interest regarding their nutritional benefits for humans in conditions such as atherosclerosis, hypertension, hyperlipidemia, obesity, diabetes, osteoporosis, arthritis and Alzheimer's disease [1][2][3][4][5][6][7][8]. A number of studies with sesame oil have reported a reduction in oxidative stress and an increase in vitamin E levels [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…With an oil content of approximately 50% within its seeds ( Uzun et al, 2008 ; Wang et al, 2014 ; Wei et al, 2015 ), sesame is an optimal candidate for industrial oil production and use. Extensive research has highlighted the nutritional advantages and health effects of sesame oil in humans, which include anti-inflammatory and anti-cancer activity, antioxidant properties, and nootropic effects ( Yokota et al, 2007 ; Monteiro et al, 2014 ; Wan et al, 2015 ; Xu et al, 2015 ; Kim et al, 2023 ). Lignans, predominantly sesame oil, are categorized into fat-soluble and water-soluble types ( Dar and Arumugam, 2013 ).…”
Section: Introductionmentioning
confidence: 99%